Discrepancy Analysis of Authentic Assessment Implementation based on Curriculum 2013 in EFL Classrooms of SMAN 1 Gianyar - ., NI WAYAN SRI NOPIANA ; ., PROF. DR. A.A.ISTRI NGR.MARHAENI,M.A.; ., DR. NI MADE RATMININGSIH, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2017)
Penelitian ini bertujuan untuk mengetahui: a) berapa tinggi kesenjangan yang terjadi pada penerapan penilaian otentik di kelas Bahasa Inggris di SMAN 1 Gianyar berdasarkan Kurikulum 2013, b) bagaimana persepsi guru terhadap penilaian otentik. Penelitian ini menggunakan Model Evaluasi Kesenjangan oleh Provus yang dimodifikasi oleh Marhaeni (2012). Subjek penelitian guru-guru Bahasa Inggris di SMAN 1 Gianyar dan objek penelitian adalah penerapan penilaian otentik. Data dalam penelitian ini dikumpulkan menggunakan lembar observasi penerapan penilaian otetik dan kuesioner persepsi guru dan dianalisis dengan Pedoman Acuan Ideal Teoretis. Hasil pada penelitian menunjukkan bahwa kesenjangan antara standar penerapan penilaian autentik dengan praktek di kelas adalah besar dengan persentase 56.77%. Secara detail, kesenjangan yang ditemukan, yaitu : 61.44% pada penilaian portfolio; 46.91%% pada penilaian kinerja; 56.90% pada penilaian proyek; 61.81%% pada penilaian diri. Selain itu, secara umum guru memiliki persepsi yang positif terhadap penilaian otentik. Berdasarkan temuan tersebut, maka dianjurkan kepada para guru, menejemen sekolah, dan pembuat kebijakan agar melakukan upaya dan pelatihan-pelatihan untuk mengurangi tingkat kesenjangan tersebut.Kata Kunci : kesenjangan, penilaian otentik, Kurikulum 2013 This evaluation study aimed at investigating: a) to what extent the discrepancy between the standard of authentic assessment implementation required by Curriculum 2013 and the practices in EFL classrooms of senior high schools based on the Curriculum 2013 in Gianyar District, Gianyar Regency is; b) what the EFL teachers’ beliefs towards the authentic assessment based on the Curriculum 2013 are. The study employed five stages of Provus’ Discrepancy Model of Evaluation modified by Marhaeni (2012). The subject of the study was three English teachers teaching in Grade 10, Grade 10 Peminatan, Grade 11, and Grade 12 in SMAN 1 Gianyar. The object of the study was the implementation of four types of authentic assessment, namely portfolio, performance, project, and self-assessments. The data were collected by means of authentic assessment implementation checklist and observation sheet based on Curriculum 2013 and teacher’s belief questionnaire and were analyzed by using The Ideal Theoretic Reference. It was found that the discrepancy in authentic assessment implementation was 56.77% which is categorized as big. In more detail, the discrepancy in implementing authentic assessment was 61.44% in portfolio assessment, 46.91% in performance assessment, 56.90% in project assessment, and 61.81% in self-assessment. In addition, the belief of teachers towards authentic assessment was positive in which authentic assessment was considered beneficial to improve students’ achievement. Based on these findings, it is recommended to the teachers, schools management, and the policy makers to do further actions in order to minimize the discrepancy and to meet the quality required by the future standards.keyword : Key words: discrepancy, authentic assessment, Curriculum 2013